تصميم مادة تعليم اللغة العربية للمرشدين السياحيين الناطقين بغيرها في ماليزيا - Abdul Hadi Abdul Rahim (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The purpose of this study is to aid the tourist guides in learning the Arabic language by designing a prototype courseware for them. This study was conducted by using systematic descriptive and analytical methodologies, where the descriptive approach required the researcher to gather information about tourism and its relativity to the field. In addition, there were several stages of scientific procedures in the analytical approach. First and foremost, learners' needs analysis was conducted before the phase of design. Secondly, experts' review analysis was conducted during the design phase. Finally, the analysis of formative evaluation by the learners after the completion of the development phase was also conducted. A special prototype courseware in learning Arabic language for the tourist guides was designed after gathering the sufficient information on tourism, and based on ADDIE instructional design model in the design and development process based on students' needs, opinions and suggestions. The participants of this study were 60 participants. Two experts were selected from the field of Education and Arabic Linguistic during the needs analysis phase. The results of this study showed that the majority of the participants were positive about learning the Arabic language for the intermediate level learners and an example of the module was completed.